Uji atraktan ekstrak daun kelapa, pisang, bambu, dan bromelia terhadap jumlah dan daya tetas telur Aedes albopictus - Eni Ritnasari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The Aedes albopictus mosquito is one of the main vectors that causes Dengue Hemorrhagic Fever (DHF) which needs to be controlled. Control using natural insecticides derived from plants is proven to be safer. The purpose of this study was to determine the effect of coconut, banana, bamboo and bromeliad leaf extracts on the number and hatchability of Aedes albopictus mosquito eggs. This type of research is an experiment with a Completely Randomized Design (CRD) pattern which was carried out in the Billfath University laboratory. The treatment consisted of extracts of banana leaves (10% DP), coconut leaves (10% DK), bamboo leaves (10% DBa), bromeliad leaves (10% DBr), control (100% water). The results showed that coconut, banana, bamboo and bromeliad leaf extracts had an effect on the number of Aedes albopictus eggs but had no effect on the hatchability of Aedes alboictus eggs, with the highest average number of eggs in the 10% bromeliad treatment of 5.42 eggs.